Economic models : an exposition - Beach, E. F. (New York : J. Wiley, 1957)
The first part of this book is very simple. The later chapters become more difficult, so that there is not a uniform level of difficulty maintained.
Includes bibliographical references and index.
osc 27/9/17
Loans
Keywords: Economics